Design and development of automatic parking system and electronic parking fee collection based on number plate recognition - Rashid, Muhammad Mahbubur; Musa, A.; Rahman, Mohammed Ataur; Farahana, Ainul F. (2011)
In this paper, automatic parking system and electronic parking fee collection based on vehicle number plate recognition is presented. This work aims to develop an automatic parking system that will increase convenience and security of the public parking lot as well as collecting parking fee without hassles of using magnetic card. The auto parking system is proposed to have less interaction of humans and use no magnetic card and its devices. Furthermore, it has parking guidance system that can show and guide user towards a parking space. The system used image processing of recognizing number plates for operation of parking and billing system. Overall, the systems run automatically to make minimum human involvement in parking system and ensure access control in restricted places. This paper presents algorithm technology based method for license plate extraction from car images followed by the segmentation of characters and reorganization and also develop electronics parking fee collection system based on number plate information.